Legal Void in the First to File Principle in the Trademark Registration System in Indonesia and Its Implications for Trademark Ownership Disputes - Oscar, Kristofer; Soesatyo, Bambang (Pelopor Publikasi Akademika, 2025)
The trademark registration system in Indonesia constitutionally adheres to the First to File principle, namely that the right to a trademark is granted to the party who first legally files for registration. However, in practice, this principle often gives rise to legal issues, especially when there is a dispute over trademark ownership between the party who registered first and the party who first used the trademark in real terms. This phenomenon indicates a legal vacuum in the trademark registration system in Indonesia, where the First to File principle does not always reflect fair and substantial legal protection for the actual trademark owner. This study aims to further analyze the weaknesses of the First to File principle, as well as to examine the extent to which the applicable legal system can protect legitimate trademark ownership, especially in the context of dispute resolution.